Does Microplastic Contamination in Agricultural Soils Decrease the Efficiency of Herbicides for Weed Control? - Maura Gabriela da Silva Brochado; Iara Barbosa Magalhães; Júlia Martins Soares; Alessandro da Costa Lima; Laura Bordignon; Allana Grecco Guedes; Mariana Ramírez Castillo; Kassio Ferreira Mendes (Microplastics)
The contamination of agricultural soils by microplastics (MPs) has significant implications for herbicide efficacy and soil health. This study investigates the effects of MPs on critical processes such as the sorption, desorption, and degradation of herbicides, highlighting their influence on these compounds’ mobility, persistence, and bioavailability. MPs interact with herbicides through sorption mechanisms, often reducing the availability of these compounds for weed control by retaining them on their surfaces. This sorption not only limits the immediate efficacy of herbicides but also alters their desorption process, resulting in a prolonged release into the soil environment. Additionally, MPs can inhibit microbial activity involved in herbicide degradation, increasing the time degradation of the half-life of these substances and extending their persistence in the environment. These processes collectively enhance the risks of bioaccumulation and environmental contamination. Understanding these interactions is essential for developing strategies to mitigate the impacts of MPs on herbicide performance and promote sustainable agricultural practices.